2008
DOI: 10.1007/s00412-008-0176-2
|View full text |Cite
|
Sign up to set email alerts
|

The ZW sex chromosomes of Gekko hokouensis (Gekkonidae, Squamata) represent highly conserved homology with those of avian species

Abstract: Populations of the gecko lizard Gekko hokouensis (Gekkonidae, Squamata) on Okinawajima Island and a few other islands of the Ryukyu Archipelago, Japan, have the morphologically differentiated sex chromosomes, the acrocentric Z chromosome and the subtelocentric W chromosome, although the continental representative of this species reportedly shows no sex chromosome heteromorphism. To investigate the origin of sex chromosomes and the process of sex chromosomal differentiation in this species, we molecularly clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(148 citation statements)
references
References 49 publications
2
145
1
Order By: Relevance
“…tawaensis, G. yakuensis, G. vertebralis, G. japonicas, G. vittatus, G. ulikovskii, G. chinensis, G. kikuchii, G. monarchus, G. petricola, G. smithii, G. subpalmatus, G. swinhonis and G. taylori (Shibaike et al 2009) and other lizards in Thailand (Satrawaha andPonkanid 1988, Wongwattana et al 2001). This is different from the study of Kawai et al (2009) and Shibaike et al (2009) that showed a ZW system (sex-chromosomes) of G. hokouensis in Japan. Geckos represent an interesting group regarding the evolution of sex determination mechanisms and include species possessing either environmental or genetic sex determination systems.…”
Section: Resultscontrasting
confidence: 91%
See 1 more Smart Citation
“…tawaensis, G. yakuensis, G. vertebralis, G. japonicas, G. vittatus, G. ulikovskii, G. chinensis, G. kikuchii, G. monarchus, G. petricola, G. smithii, G. subpalmatus, G. swinhonis and G. taylori (Shibaike et al 2009) and other lizards in Thailand (Satrawaha andPonkanid 1988, Wongwattana et al 2001). This is different from the study of Kawai et al (2009) and Shibaike et al (2009) that showed a ZW system (sex-chromosomes) of G. hokouensis in Japan. Geckos represent an interesting group regarding the evolution of sex determination mechanisms and include species possessing either environmental or genetic sex determination systems.…”
Section: Resultscontrasting
confidence: 91%
“…Gecko populations without males were first discovered followed by seven parthenogenetic species (Smith 1935, Ota 1989b, Volobouev et al 1993), including triploid (3n) forms in some populations (Moritz 1984). A ZW system was recently revealed in Gekko hokouensis, and the genetic content of its sex chromosomes was found to be similar to that of the avian Z chromosome (Kawai et al 2009, Shibaike et al 2009 Meiotic cell division of G. gecko The present study on meiotic cell division in G. gecko found that during metaphase I (meiosis I, reductional division) the homologous chromosomes showed synapsis, which can be defined as the 19 ring bivalents (3 ring bivalents of metacentric, 2 ring bivalents of submetacentric, 1 rod bivalent of acrocentric, and 13 rod bivalent of telocentric chromosomes) and 19 haploid chromosomes at metaphase II (meiosis II, equational division) as a diploid species (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…As far as we know, sex chromosomes of lacertids are not homologous with those of other sauropsid lineages with known gene content, such as advanced snakes (Matsubara et al, 2006;Vicoso et al, 2013), iguanas (see, for example, Alföldi et al, 2011;Rovatsos et al, 2014a-c), geckos (Kawai et al, 2009), turtles (see, for example, Kawagoshi et al, 2012Kawagoshi et al, , 2014 and birds (see, for example, Zhou et al, 2014). The lacertid Z chromosome partially shares gene content with the ancestral therian X, and thus we assume that these sex chromosome systems probably evolved from the same ancestral chromosome (syntenic block).…”
Section: Identification Of Putative Z-specific Genesmentioning
confidence: 99%
“…In any case, more robust testing of the hypotheses of the ancestral sex determination and on the evolution of sex-determining mechanisms in amniotes is largely precluded by our very limited knowledge about the homology of sex chromosomes and sex-determining genes among particular groups. The homology of sex chromosomes can be inferred from the knowledge of the gene content of sex chromosomes; however, it has been identified in only a few amniote lineages such as viviparous mammals (see, for example, Kohn et al, 2004) and monotremes (see, for example, Rens et al, 2007), birds (see, for example, Zhou et al, 2014), several turtle species (see, for example, Kawagoshi et al, 2012Kawagoshi et al, , 2014, advanced snakes (Matsubara et al, 2006;Vicoso et al, 2013;Rovatsos et al, 2015), iguanas (see, for example, Alföldi et al, 2011;Rovatsos et al, 2014a-c), a gecko (Kawai et al, 2009) and recently also a lacertid lizard (Srikulnath et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Of considerable interest is a gecko species (Gekko hokouensis) with a ZW system that shares homology with the bird ZW system (Kawai et al, 2009). Thus, there are at least three sex chromosome systems, in distantly related vertebrate groups (monotremes, birds and geckos), which share extensive homology.…”
Section: Sex Chromosomes Of Birds Snakes and Lizardsmentioning
confidence: 99%